A study on teenagers' perceptions of the gender roles and stereotypes found in contemporary Disney animated films - Abad, Rowena A.; Tamayo, Melissa Mae P.; Tungcul, Lyca Marie A. (2013)
This research aims to answer the general problem, how do teenagers perceive the gender stereotypes of women and men in contemporary Disney animated films,particularly in Princess and the frog, Tangled and Brave. Interviews were used to determine the effects of contemporary Disney animated films The Princess and the frog, Tangled and Brave on teenagers' perception about gender roles and stereotypes. Interviewed were fifteen(15) teenagers, eight(8) female and seven(7) males from different schools. Researchers concluded that Disney animated films could influence a teenager's perception. The changes in gender stereotypes in the films were recognized and could be found in the society. The teenagers are conscious of the messages found in the Disney contemporary films, The Princess and the frog, Tangled and Brave. They are aware about the implications of social relationships and roles that were presented in the films. Their views such as their need for gender equality have been strengthened and heightened by the Disney films portrayal of men and women. Changes in gender roles and stereotypes are evident in these contemporary animated films. The teenagers see women now as tough and determined persons, will-driven and can stand on their own feet. Men, the respondents say, seem to be dependent on women. The respondents believe in and accept the changes that come with time. In the end, the respondents all agreed that these changes in both sexes compliment each other -- Author's abstract.